DIGITAL PARENTING DALAM PERSPEKTIF PENDIDIKAN ISLAM - Suriadi Adi Samsuri (Program Studi PAI STAI Al Falah Banjarbaru, 2023)
Abstract: The impact of the corona virus 19 pandemic has brought a big and urgent change in various sectors, one of which is in educational institutions ranging from elementary to tertiary level. This article discusses digital parenting during a pandemic. This study focuses on (1) digital parenting implementation by parents during a pandemic, (2) digital parenting steps taken by parents, (3) supporting and inhibiting factors in digital parenting during a pandemic. This research was conducted in Lubuk Dagang Village, Sambas District, Sambas District, West Kalimantan Province. The research approach used is a qualitative approach. The subjects of this study were parents and children. While the data collection techniques in this study used observation, interviews and documentation. The results of this study show that (1) implementation of digital parenting by (a) providing restrictions on using smartphones, (b) giving punishment, (c) prohibiting activities that are not good on social media, (2) digital parenting steps by (a) providing time limits on using smartphones are carried out during study hours and prayer hours, (b) Give punishment if children do not comply with regulations such as posting and opening inappropriate sites, parents will not buy quotas anymore and confiscate children's personal smartphones, (c) giving advice, (3) supporting factors including giving advice to children, limiting the hours children use smartphones, while inhibiting factors include not all parents mastering technology, limited time for parents to educate children due to work, environmental factors. Keywords: Digital Parenting, Islamic Education. Abstrak: Dampak pandemi corona virus 19 ternyata telah membawa sebuah perubahan yang besar dan mendesak pada berbagai sektor, satu diantaranya adalah pada lembaga pendidikan mulai dari tingkat dasar hingga Perguruan Tinggi. Artikel ini membahas tentang digital parenting pada masa pandemi. Kajian ini terfokus pada (1) impelementasi digital parenting yang dilaukan oleh orangtua pada masa pandemi, (2) langkah-langkah digital parenting yang dilakukan orang tua, (3) faktor pendukung dan penghambat dalam digital parenting pada masa pandemi. Penelitian ini dilakukan di Desa Lubuk Dagang Kecmatan Sambas Kabupaten Sambas Provinsi Kalimantan Barat. Pendekatan penelitian yang digunakan pendekatan kualitatif. Subyek penelitian ini yakni orangtua dan anak. Sedangkan teknik pengumpulan data dalam kajian ini menggunakan observasi, wawancara dan dokumentasi. Hasil Penelitian ini menunjukan bahwa (1) implementasi digital parenting dengan (a) memberikan batasan menggunakan smartphone, (b) memberikan hukuman, (c) melarang kegiatan yang tidak baik di media sosial, (2) langkah digital parenting dengan cara (a) memberikan batasan waktu dalam menggunakan smartphone dilakukan pada saat jam belajar dan jam sholat, (b)Memberikan hukuman jika anak tidak menaati peraturan seperti memposting serta membuka situs-situs yang tidak pantas maka orangtua tidak akan membelikan kuota lagi dan menyita smartphone pribadi anak, (c) memberikan nasihat, (3) faktor pendukung diantaranya memberikan nasihat kepada anak, membatasi jam anak menggunakan smartphone, sedangkan faktor penghambat diantaranya tidak semua orangtua menguasai teknologi, keterbatasan waktu orangtua dalam mendidik anak karena bekerja, faktor lingkungan. Kata Kunci: Digital Parenting, Pendidikan Islam.